Associations between economic distress and African-American adolescents' social competence: an examination of two models - Ashiabi, Godwin Samuel (2002)
This study, using the third wave of data from the Woodlawn Mental Health Longitudinal Community Epidemiological Project, 1966-1976, examined two models that focused on the processes through which economic distress impacts African-American adolescents' social competence. Only the responses of African-American participants and family types that included mothers were used, resulting in a total sample size of 840 families and four family types. The first model, Model A, examined the moderating roles of family structure and locus of control orientation on the associations among economic distress, maternal mood problems, and family processes, on African-American adolescents' antisocial behaviors and depression. Using path analysis with maximum likelihood estimation, I found that (a) the same structural model holds across family type and locus of control orientation; (b) the effects of maternal mood problems on adolescents' social competence differed by family type; (c) the effects of family processes on adolescents' social competence differed by family type; and (d) the effects of family processes on adolescents' social competence differed by locus of control orientation. The second model, Model B, examined the differential effects of adolescent temperament, gender, and family type on the associations among economic distress, maternal mood problems, family processes, association with deviant peers, and antisocial behaviors. Using path analysis with maximum likelihood estimation revealed that (a) the same structural model holds across temperament, gender; and family type; (b) the effects of family process on antisocial behaviors differed by temperament; (c) the effects of family processes on antisocial behaviors differed by family type; and (d) there were no gender differences evident